Daya Terima Bakpia dengan Penambahan Tepung Pati Ganyong dan Tepung Ikan Lele Sebagai Snack Tinggi Energi Tinggi Protein untuk Remaja: Acceptability of Bakpia with the Addition of Ganyong Starch Flour and Catfish Flour as a High Energy High Protein Snack for Adolescent - Nurhafifa, Gusti Madya; Telisa, Imelda; Muzakar, Muzakar (UNIVERSITAS NGUDI WALUYO, 2025)
Chronic Energy Deficiency is a condition of nutritional problems that occurs due to an imbalance in energy and protein intake over a long period of time. Teenagers need good nutritional intake to meet their needs. Unfulfilled nutritional intake will cause nutritional problems. Efforts to provide adolescents with nutritious food can be done by providing distractions that are high in energy and high in protein. To find out the formulation, acceptability and analysis of macro nutrients (carbohydrates and protein). This research method is an experiment with a non-factorial Completely Randomized Design (CRD) with organoleptic tests on 30 untrained panelists. Furthermore, a nutritional content test was carried out using proximate analysis. The energy content of bakpia canna starch flour and catfish flour per is 391.06 Kcal, protein 9.21%, fat 17.02%, carbohydrates 50.26% in 100 g bakpia. Based on the Kruskal wallis test, there was a significant influence between the acceptability of bakpia with canna starch flour and catfish flour on taste and aftertaste. The results of the research show that bakpia canna starch flour and catfish flour can be used as an alternative high-energy, high-protein snack. ABSTRAK Kekurangan Energi Kronis merupakan suatu kondisi masalah gizi yang terjadi akibat adanya ketidakseimbangan asupan energi dan protein dalam jangka waktu yang lama. Remaja membutuhkan asupan gizi yang baik untuk memenuhi kebutuhannya. Asupan gizi yang tidak terpenuhi akan menyebabkan masalah gizi Upaya pemenuhan makanan bergizi pada remaja dapat dilakukan dengan pemberian selingan yang tinggi energi dan tinggi protein. Penelitian ini bertujuan untuk mengetahui formulasi bakpia, daya terima serta analisis zat gizi makro (Karbohidrat dan protein). Metode penelitian ini adalah eskperimen dengan Rancangan Acak Lengkap (RAL) non factorial dengan uji organoleptik pada panelis tidak terlatih sebanyak 30 orang. Penentuan nilai gizi menggunakan analisis proksimat. Formula bakpia tepung pati ganyong dan tepung ikan lele yang terpilih adalah F1 (70:30). Kandungan energi bakpia tepung pati ganyong dan tepung ikan lele per 100 gram yaitu 391,06 Kkal, protein 9,21 %, lemak 17,02 %, karbohidrat 50,26 %.. Berdasarkan uji Kruskal wallis terdapat pengaruh yang signifikan antara daya terima bakpia tepung pati ganyong dan tepung ikan lele dengan Rasa dan Aftertaste. Hasil penelitian menunjukkan bakpia tepung pati ganyong dan tepung ikan lele ini bisa digunakan sebagai alternatif selingan tinggi energi tinggi protein.